Substitution of sodium silicate with rice husk ash-NaOH solution in metakaolin based geopolymer cement concerning reduction in global warming. (20th January 2017) - Kamseu, E.; Beleuk à Moungam, L.M.; Cannio, M.; Billong, Ndigui; Chaysuwan, Duangrudee; Melo, U. Chinje; Leonelli, C.
Abstract: Rice husk ash (RHA), a by-product from the rice industry, was used as principal source of amorphous silica for the production of sodium silicate solution (MR ∼ 3) used for the replacement of standard commercial sodium silicate in the mix-design of metakaolin based geopolymer composites. Three initial concentrations of NaOH were considered (8, 10 and 12 M) with the aim to investigate on the optimum dissolution and formation of silica oligomers capable to act as binder during the geopolymerization. Results (FT-IR and XRD) showed that RHA-NaOH sodium silicate solutions have characteristics similar to that of standard commercial sodium silicate and the residual carbonates present in the viscous pastes can be monitored during the preparation of geopolymers using the mix-design. Combined 25 vol% standard sodium silicate solution with ∼75 vol% of RHA-NaOH based sodium silicate solution conducted to good polycondensation, densification, high flexural strength (∼8 MPa) and low porosity similar to that of the standard matrix of metakaolin based composites. The new approach is found promising for the significant reduction of the Global Warming Potential of Geopolymers. Graphical abstract: Highlights: RHA-NaOH sodium silicate have similar characteristics to that of standard one. 75 vol% of standard sodium silicate replaced with RHA-NaOH as a sustainable binder. Using RHA-NaOH sodium silicates for geopolymers manufacture reduce the GWP.